Pilot-scale production of lipase using palm oil mill effluent as a basal medium and its immobilization by selected materials - Asih, Devi Ratna; Alam, Md Zahangir; Salleh, Md. Noor; Salihu, Aliyu (Japan Oil Chemists' Society, 2014)
A pilot-scale production of lipase using palm oil mill effluent (POME) as a fermentation basal medium was carried out, and parameters for immobilization of the produced lipase were optimized. Lipase production in a 300-L bioreactor was performed using two proposed strategies, constant power per volume (P/V) and constant tip speed. Moreover, lipase immobilization on different materials was also investigated. Lipase production was performed using liquid-state bioconversion of POME as the medium and Candida cylindracea as the inoculum. The fermentation medium was composed of 1% total suspended solids (TSS) of POME, 0.5% (w/v) peptone, 0.7% (v/v) Tween-80, and 2.2% inoculum. The medium composition was decided on the basis of the medium optimization results of a previous study. The fermentation was carried out for 48 h at 30°C and pH 6. The maximum lipase production was 5.72U/mL and 21.34 U/mL, obtained from the scale-up strategies of constant tip speed and P/V, respectively. Four accessible support materials were screened for their potential use in immobilization. The most suitable support material was found to be activated carbon, with a maximum immobilization of 94%.